Gramsci : space, nature, politics - Ekers, Michael, 1978- (Chichester ; Malden, MA : Wiley-Blackwell, 2013)
'This unique collection is the first to bring attention to Antonio Gramsci's work within geographical debates. Presenting a substantially different reading to Gramsci scholarship, the collection forges a new approach within human geography, environmental studies and development theory.'--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Gramsci, Antonio, -- 1891-1937.; Gramsci, Antonio, -- 1891-1937.; Gramsci, Antonio, -- 1891-1937.; Communism -- Italy; Marxian historiography; Philosophy, Marxist; Political science -- Philosophy; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism; Communism; Marxian historiography; Philosophy, Marxist; Political science -- Philosophy; Italy; Electronic books; Electronic books